A dataset of 137Cs activity concentration and inventory in forests contaminated by the Fukushima accident - Shoji Hashimoto (Nature Portfolio, 2020)
Measurement(s) activity (of a radionuclide) • Cesium Cs 137 Technology Type(s) digital curation Factor Type(s) geographic location Sample Characteristic - Organism Cryptomeria japonica • Chamaecyparis obtusa • Pinus densiflora • Quercus serrata Sample Characteristic - Environment temperate evergreen needleleaf forest • temperate deciduous broadleaf forest • leaf • wood • litter layer • forest soil • mushroom (food source) • bark • pollen Sample Characteristic - Location Japan • Fukushima Prefecture Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.13166462